2020
DOI: 10.1186/s13071-020-04196-x
|View full text |Cite
|
Sign up to set email alerts
|

A daf-7-related TGF-β ligand (Hc-tgh-2) shows important regulations on the development of Haemonchus contortus

Abstract: Background: In most multicellular organisms, the transforming growth factor-β (TGF-β) signalling pathway is involved in regulating the growth and stem cell differentiation. Previous studies have demonstrated the importance of three key molecules in this pathway in the parasitic nematode Haemonchus contortus, including one TGF-β type I receptor (Hc-tgfbr1), one TGF-β type II receptor (Hc-tgfbr2), and one co-Smad (Hc-daf-3), which regulated the developmental transition from the free-living to the parasitic stage… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…3E). These results suggest a role of HcSMA2 in differentiation of infective xL3 to L4 larvae, which is consistent with the function of the known members of the TGF-β and Insulin signaling [8][9][10][11][12]23]. In C. elegans, CeSMA2 regulates the body size [24], morphogenesis of the male worm's tail tip [25], as well as reproductive aging [21,26].…”
Section: Hcsma2 Transcript Is Upregulated In the Adult Male Wormssupporting
confidence: 70%
See 1 more Smart Citation
“…3E). These results suggest a role of HcSMA2 in differentiation of infective xL3 to L4 larvae, which is consistent with the function of the known members of the TGF-β and Insulin signaling [8][9][10][11][12]23]. In C. elegans, CeSMA2 regulates the body size [24], morphogenesis of the male worm's tail tip [25], as well as reproductive aging [21,26].…”
Section: Hcsma2 Transcript Is Upregulated In the Adult Male Wormssupporting
confidence: 70%
“…In Haemonchus contortus, previous work demonstrating the important roles of DAF7 signaling during larval development of this economically important nematode parasite has focused on TGF-β ligand [8], TGF-β type I receptor [9], TGF-β type II receptor [10]), TGF-β-regulated R-SMAD [11] and Co-SMAD [12]. Little is known about BMP (DBL1) signaling in this parasite, however.…”
Section: Introductionmentioning
confidence: 99%
“…These possibilities may be clarified further by the creation of a full Ppa-daf-7 null mutant consisting of mutations in all seven Ppa-daf-7 paralogues. Importantly, due to the similarities between the dauer stage in free-living nematodes and the infective larvae in parasitic nematode species, the presumed association of TGF-β signaling with dauer formation has formed the basis for substantial parasitic research as a potential target to understand their infectivity ( McSorley et al 2009 ; Ogawa et al 2009 ; Crook et al 2010 ; Ma et al 2019 ; Yang et al 2019 ; He et al 2020 ). Therefore, functional studies in other nematode species will be essential to distinguish between these possibilities, and further inform research on parasitic nematodes.…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the similarities between the dauer stage in free-living nematodes and the infective larvae of many parasitic nematode species ( Viney et al 2005 ; Gilabert et al 2016 ). As such, several TGF-β family members have been identified in parasitic nematodes, although functional studies are problematic due to the complex life cycles found in these organisms ( McSorley et al 2009 ; Ogawa et al 2009 ; Crook et al 2010 ; Ma et al 2019 ; Yang et al 2019 ; He et al 2020 ). Interestingly, a recent study in P. pacificus demonstrated that the Ppa-daf-7 pathway is necessary for bacterial induced gut–brain communication, which in turn enhanced numerous developmental phenotypes ( Lo et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Hc-tgh-2 gene is expressed by all developmental stages, with iL3 expressing the most. Hc-TGH-2 seems to play an important role in the transition from the free-living to parasitic stage, as well as in digestion, absorption, and reproductive development, based on the localisation of the ligand in parasite body [ 61 ].…”
Section: Tgfβ Signalling In Helminthsmentioning
confidence: 99%